Phenylene bridged cyclic azaacenes: dimers and trimers - Hahn, Sebastian; Koser, Silke; Hodecker, Manuel; Seete, Pascal; Rominger, Frank; Dreuw, Andreas; Bunz, Uwe H. F. (Chemistry - a European journal, 2018)
The synthesis and characterization of novel macrocyclic, phenylene-bridged azaacenes is reported. These species were obtained either by a conventional benzoin- diamine condensation, as shown for the case of the cyclotrimers, in which the azaacene units are separated by meta-connected phenylene bridges, or by a Buchwald-Hartwig-type Pd-catalyzed coupling, which employs 1,2,5,6-tetrabromodibenzocyclooctatetraene as the substrate and bis-TIPS-ethynylated diaminobenzene, -naphthalene or -anthracene as the coupling partner to give the double coupling products azaacene-annulated dibenzocyclooctatetraenes in moderate yields. The macrocycles show strong emission and light emitting diodes have been built with brightnesses exceeding 1600 cd m−2. We evaluated the optical and electronic properties and the solid-state structures of the molecules and discuss their properties through comparison with their linear and tetrameric N-heteroacene counterparts.